Тонкi плiвки ZnO, отриманi методом АПО, як матерiал для фотовольтаїки - Semikina, T. V.; Mamykin, S. V.; Sheremet, G. I.; Shmyreva, L. N. (Publishing house "Academperiodika", 2019)
The tasks to be solved while developing solar cells have been reviewed. The analysis of technological methods used for the fabrication of thin transparent conducting ZnO films from the viewpoint of their application in organic and thin-film solar cells demonstrates the advantage of the atomic layer deposition method. It is shown that this method provides a low-temperature (100–200 ∘C) growth of films with a required resistivity of about 10−3 Ω·cm and a transparency of 85–90%. The application of ZnO films in organic photovoltaic structures improves the time stability of their rectification characteristics. The investigation of organic structures with ZnO as a cathode or an anode showed the potential of the usage of ZnO as a cathode. The study of ZnO as a transparent conductive electrode in a CdTe-based inorganic photovoltaic structure shows an increase in the photocurrent and a decrease in the recombination in comparison with a Mo electrode.